HADITS DHA’IF SEBAGAI HUJJAH DALAM PERSPEKTIF IBNU HAJAR AL-ASQALANI DAN AL-ALBANI: STUDI KOMPARATIF ANALITIS - Dhiya Azhomah Romadhona; Romlah Abu Bakar Askar; Miftahuddin Miftahuddin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2026)
Da'if hadith represents the most debated category in islamic scholarly tradition, particularly regarding its permissibility as a hujjah (legal proof) in both legal rulings and religious practice. this study aims to examine and compare the views of two prominent hadith scholars, ibn hajar al-asqalani and muhammad nashiruddin al-albani, on the status of da'if hadith as hujjah. a qualitative approach was employed through library research and comparative-analytical methods, drawing on primary sources from the authoritative works of both scholars and secondary sources comprising relevant academic journals and literature. the findings reveal that ibn hajar permitted the use of da'if hadith in the context of fadha'il al-a'mal, mau'izhah, targhib, tarhib, and i'tibar, subject to three strict conditions, reflecting a contextual paradigm in line with the consensus of classical scholars. al-albani, by contrast, rejected the use of da'if hadith entirely and without exception, on the grounds that such hadith yields only unverifiable conjecture. the divergence between the two scholars is not merely a matter of technical methodology, but reflects two fundamentally different paradigms regarding the function of hadith in religious life. this study contributes to filling a scholarly gap by systematically bringing both perspectives together within a single comparative framework.